RANCANG BANGUN SISTEM KONTROL MINIATUR ALAT PEMINDAH MATERIAL PADA PROSES DISTRIBUSI BIJIH NIKEL MENGGUNAKAN PLC - Abdul Haris Mubarak; Moh Afandy; Muhammad Khaidir (Jambura Physics Journal, 2023)
This research aims to make a miniature ore material transfer tool automatically using Omron PLC. The way this tool works is that when the start button is pressed, motor 1 will move the apron containing the ore to be taken to the 3 storage barrels to be filled alternately. In each storage barrel, a proximity sensor is installed to detect the level of ore filling. On the rails that are passed by the apron, there are three limit switches that serve as indicators that the position of the apron is right above the storage barrel, then motor 2 will open the valve on the apron so that the ore on the apron falls into the reservoir. From this research, we have succeeded in obtaining an automatic control system for a miniature material transfer device in the ore distribution process.